EXPLORATION OF POTENTIAL ANTIBACTERIAL PLANTS IN HERBAL CONDITIONS AGAINST (STAPHYLOCOCCUS EPIDERMIDIS) THE CAUSE OF BODY ODOR: EXPLORATION OF POTENTIAL ANTIBACTERIAL PLANTS IN HERBAL CONDITIONS AGAINST (STAPHYLOCOCCUS EPIDERMIDIS) THE CAUSE OF BODY ODOR - yuliana; Windiyati; Nurul Arriza; Nurul Arriza; Melyani; Alexander, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Introduction: herbal concoctions from beluntas leaves, betel leaves, ginger and kandis acid are known to have activity against the bacteria that causes body odor, Staphylococcus epidermidis, so it is possible that it can be used to eliminate body odor. Method: Quasi Experimental research type with Pretest-Posttest Nonequivalent Control Group Design. Held at the STIKES Panca Bhakti Pontianak Dormitory on 14-28 November 2023. The sample was 26 female students at the Stikes Panca Bhakti dormitory and had body odor problems, the respondents were randomly divided into 2 groups, teenagers in the intervention group were given herbal body odor test materials with a dose of 1x1 suchet (25 grams) and teenagers in the control group were given the comparison agent Detol, the research was carried out for 14 days. Results: organoleptic test regarding the taste of body odor herbal medicine, almost all panelists liked the taste of body odor herbal medicine, namely 20 people (77%), regarding the aroma of body odor herbal medicine, most of the panelists liked the aroma of body odor herbal medicine, namely 16 people (61.6 %), regarding the form of body odor herbal medicine, some of the panelists really liked the form of body odor herbal medicine, namely 11 people (42.3%) and the P-value was 0.000 < 0.005 which shows that there is a difference in the effectiveness of providing body odor herbal medicine in the intervention and fluid administration groups. detol in the control group. Conclusion: Body odor herbal medicine (exploration of beluntas leaves, ginger, green betel and kandis acid) is effective in reducing body odor in adolescents